Design, Optimization and Energetic Evaluation of an Efficient Fully Powered Ankle-Foot Prosthesis With a Series Elastic Actuator - Dianbiao Dong; Wenjie Ge; Bryan Convens; Yuanxi Sun; Tom Verstraten; Bram Vanderborght (IEEE Access, 2020)
The use of powered ankle-foot prostheses for below-knee amputees leads to challenges like the peak power of the applied actuator and biomechanical features of the prosthesis foot. This paper proposes an efficient powered ankle-foot prosthesis with a series elastic actuator. By combining the geared five-bar spring (GFBS) mechanism and the traditional series elastic actuator (SEA), a series elastic with geared five-bar (SGFB) actuator is built. The new SGFB actuator has the benefits of both the GFBS and the SEA on mimicking biomechanics of the human ankle and reducing the peak power of the motor. The healthy walking gait in the experiment results indicates that the optimized SGFB prosthesis foot including a 150W Maxon DC motor can provide a 70kg subject enough net positive energy with an energy efficiency of 35.3% during normal speed walking in the treadmill trials. The experiment of the SGFB prosthesis foot in semi-active mode shows the advantage on closely mimicking the human biomechanics during the control dorsiflexion phase and the importance of injecting positive energy during the powered plantarflexion phase. The experiment results also show that the optimization of different parameters within the electromechanical model considering the efficiency of the whole drive train can effectively reduce the motor's peak power to 132 W by making the motor more effective in high-power conditions.